A hierarchical multi-scale framework and indicators of hydromorphological processes and forms - Gurnell, Angela M.; Bussettini, Martina; Camenen, Benoit; González del Tánago, Marta; Grabowski, Robert C.; Hendriks, Dirk; Henshaw, A.; Latapie, A.; Rinaldi, Massimo; Surian, Nicola (European Commission within the 7th Framework Programme, 2014)
Background and Introduction to Deliverable 2.1. Work Package 2 of REFORM focuses on hydromorphological and ecological processes and interactions within river systems with a particular emphasis on naturally functioning systems. It provides a context for research on the impacts of hydromorphological changes in Work Package 3 and for assessments of the effects of river restoration in Work Package 4. Deliverable 2.1 of Work Package 2 proposes a hierarchical framework to support river managers in exploring the causes of hydromorphological management problems and devising sustainable solutions. The deliverable has four parts. Part 1 (this volume) provides a full description of the hierarchical framework and describes ways in which each element of it can be applied to European rivers and their catchments. Part 2 includes thematic annexes which provide more detailed information on some specific aspects of the framework described in Part 1. Part 3 includes catchment case studies which present the application of the entire framework described in Part 1 to a set of European catchments located in different biogeographical zones. Part 4 includes catchment case studies which present a partial application of the framework described in Part 1 to a further set of European catchments.